Alienation in Scapegoat novel by Elie Amir - Rasheed, Ali Mohamed (Al-Adab Journal, 2021)
This study aims to study the phenomenon of alienation in the novel " Scapegoat " by Elie Amir, because this phenomenon appears more clear in this novel, and it represents a current that dominates its data and intellectual and artistic trends, especially that the writer was able to embody this pivotal phenomenon distinctive technical embodiment, and revealed The nature of the relationship between the real world and the dream world of personalities, and the contradictory, opposing, collision and sense of frustration, loss and alienation that characterize it. The study included the following axes: Amir’s reality and conditions of his life. The concept of alienation. Alienation in fiction. Intellectual data in the novel. Manifestations of alienation in the novel. Narrative techniques and their role in highlighting the experience of alienation.